2022
DOI: 10.1111/add.16003
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol: No Ordinary Commodity—a summary of the third edition

Abstract: Background and AimsThis article summarizes the findings and conclusions of the third edition of Alcohol: No Ordinary Commodity. The latest revision of this book is part of a series of monographs designed to provide a critical review of the scientific evidence related to alcohol control policy from a public health perspective.DesignA narrative summary of the contents of the book according to five major issues.FindingsAn extensive amount of epidemiological evidence shows that alcohol is a major contributor to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 87 publications
1
21
0
5
Order By: Relevance
“…Our systematic review shows that, consistent with prior research, 8 , 9 , 10 alcohol control policies that raise alcohol prices and reduce the temporal availability of alcoholic beverages lead to a reduction in overall alcohol consumption, with some differential effects identified across sociodemographic groups. Specifically, we found that doubling alcohol excise taxes or introducing a MUP of about Int$ 0.90 per 10 g of pure alcohol results in an average 10% decrease in the level of alcohol consumption within the same year, with potentially larger reductions in low-income compared to more affluent groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our systematic review shows that, consistent with prior research, 8 , 9 , 10 alcohol control policies that raise alcohol prices and reduce the temporal availability of alcoholic beverages lead to a reduction in overall alcohol consumption, with some differential effects identified across sociodemographic groups. Specifically, we found that doubling alcohol excise taxes or introducing a MUP of about Int$ 0.90 per 10 g of pure alcohol results in an average 10% decrease in the level of alcohol consumption within the same year, with potentially larger reductions in low-income compared to more affluent groups.…”
Section: Discussionsupporting
confidence: 81%
“…5 Three policies, the so-called “best buys”, stand out in not only being the most cost-effective policies, but also relatively easy to implement: increasing alcohol prices through taxation or minimum pricing, restricting the temporal and spatial availability of alcoholic beverages, and bans and restrictions of alcohol marketing. 6 , 7 , 8 However, two key questions have not yet been addressed in prior reviews: First, a quantification of their impact on consumption in real-world settings is pending, although their effectiveness, particularly in reducing alcohol-attributable harm, has been well established (for the most recent systematic reviews, see 9 , 10 , 11 ). Second, while systematic differences in both the drinking patterns and the related harms have been observed across both SES 12 , 13 and racial and ethnic groups, 14 , 15 there has been minimal investigation into whether these policies can mitigate against growing inequalities in the alcohol-attributable disease burden through differential effects on alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest a need to identify ways in which policy can tackle inequalities in alcohol-attributable harm (Katikireddi et al, 2017). The evidence base suggests that reducing alcohol availability is a promising cost-effective policy initiative to reduce alcohol-related harm, including violence (Babor, 2010; Babor et al, 2010; Foster et al, 2017; WHO, 2009a, 2009b), yet initiatives for addressing the unequal distribution of such harm remain rare. It is important that we understand the distribution of such harms by area deprivation to assist with this endeavour, because those from more deprived areas not only suffer disproportionately from the harm associated with alcohol consumption (Mäkelä and Paljärvi, 2008; Sadler et al, 2017), but may also be less likely to object in the licensing process owing to barriers such as access to services and education.…”
Section: Discussionmentioning
confidence: 99%
“…The European Union is the region with the highest level of alcohol consumption with seven out of the 10 countries with the highest alcohol consumption being member states (WHO Global Health Observatory, 2019 ). To reduce alcohol‐related harm, different policy options have been proposed, with pricing policies, availability and marketing restrictions usually considered as most effective and cost‐effective (Babor et al., 2022 ; Chisholm et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%